Dietary Fructose Inhibits Intestinal Calcium Absorption and Induces Vitamin D Insufficiency in CKD - Douard, Veronique (American Society of Nephrology, 2010)
Renal disease leads to perturbations in calcium and phosphate homeostasis and vitamin D metabolism. Dietary fructose aggravates chronic kidney disease (CKD), but whether it also worsens CKD-induced derangements in calcium and phosphate homeostasis is unknown. Here, we fed rats diets containing 60% glucose or fructose for 1 mo beginning 6 wk after 5/6 nephrectomy or sham operation. Nephrectomized rats had markedly greater kidney weight, blood urea nitrogen, and serum levels of creatinine, phosphate, and calcium-phosphate product; dietary fructose significantly exacerbated all of these outcomes. Expression and activity of intestinal phosphate transporter, which did not change after nephrectomy or dietary fructose, did not correlate with hyperphosphatemia in 5/6-nephrectomized rats. Intestinal transport of calcium, however, decreased with dietary fructose, probably because of fructose-mediated downregulation of calbindin 9k. Serum calcium levels, however, were unaffected by nephrectomy and diet. Finally, only 5/6-nephrectomized rats that received dietary fructose demonstrated marked reductions in 25-hydroxyvitamin D(3) and 1,25-dihydroxyvitamin D(3) levels, despite upregulation of 1α-hydroxylase. In summary, excess dietary fructose inhibits intestinal calcium absorption, induces marked vitamin D insufficiency in CKD, and exacerbates other classical symptoms of the disease. Future studies should evaluate the relevance of monitoring fructose consumption in patients with CKD.